KARAKTERISTIK RUMAH TIDAK LAYAK HUNI BERDASARKAN SOSIAL MASYARAKAT DI KECAMATAN KOTO TANGAH KOTA PADANG - chika andri sani; Endah Purwaningsih (JURUSAN GEOGRAFI FIS UNP, 2023)
ABSTRACT This study aims to: (1) find out the social community of uninhabitable houses in Koto Tangah District, Padang City. (2) presents data on uninhabitable houses in the form of web-gis in Koto Tangah District, Padang City. This research is a quantitative descriptive study. Data collection techniques are carried out in three stages, namely: (1) observation techniques that are useful for observing an object to be studied either directly or indirectly. (2) interviews that are useful for obtaining information by means of questions and answers between the questioner and the resource person, namely the head of the household, the house is unfit for habitation. (3) documentation is used to obtain data on things or related to the research topic, including population, weather, maps and those related to uninhabitable houses, data analysis techniques with data editing stages, data percentages. Based on research results 1) there are 46 data on uninhabitable houses in Koto Tangah District, Padang City, into 3 groups of house conditions, namely (1) the group of houses with the status of land that is not owned by themselves but the condition of the house deserves to be given home rehabilitation assistance as much as 15.21%. (2) the group of houses with the status of self-owned land with the condition of the house not being so damaged as much as 60.86%. (3) the group of houses where the condition of the house is still good as much as 23.91% so that they do not need to be given assistance to rehabilitate uninhabitable houses. 2) Presentation of data in the form of web GIS can be accessed via the following link: https://gcp-australia-southeast1.app.carto.com/map/3064128e-e5a7-4358-a132-4b2a3885c034. Keywords: uninhabitable houses, rehabilitation